Sprayable copper and copper–zinc nanowires inks for antiviral surface coating. Issue 10 (21st February 2022) - Pan, Chaochao; Phadke, Kruttika S.; Li, Zheng; Ouyang, Gaoyuan; Kim, Tae-hoon; Zhou, Lin; Slaughter, Julie; Bellaire, Bryan; Ren, Shenqiang; Cui, Jun
Abstract : SEM and TEM images of copper and copper–zinc nanowires that are sprayable for antiviral surface coating. Abstract : Copper alloys are known for their high antimicrobial efficacy. Retrofitting high-touch surfaces in public space with solid copper components is expensive and often impractical. Directly coating copper onto these high-touch surfaces can be achieved with hot or cold spray, but the procedure is complicated and requires special equipment. This article reports on the development of sprayable copper and copper–zinc nanowire inks for antiviral surface coating applications. Our results show that copper nanowires inactivate the SARS-CoV-2 virus faster than bulk copper. And a trace amount of zinc addition has a significant effect in enhancing the virucidal effect. More importantly, these nanowire inks are sprayable. They can be easily applied on high-touch surfaces with a spray can. When combined with common chemical disinfectants, the copper-based nanowire ink spray may prolong the disinfecting effect well after application.